Edukasi Penyebaran Kuman Penyebab Penyakit pada Anak-Anak di SDN 07 Palmerah, Jakarta: Education on the spread of Germs Causing Diseases among Children at SDN 07 Palmerah, Jakarta - Ayu, Ira Marti; Situngkir, Decy; Nitami, Mayumi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Children are a vulnerable group to infectious diseases, which are the leading cause of death among them. Data from Palmerah Community Health Centre (Puskesmas Palmerah) showed that 6 of the ten most common illnesses are infectious diseases, such as colds (acute nasopharyngitis), fever, cough, flu, and gastrointestinal issues (diarrhea and gastroenteritis of presumed infectious origin). Based on these issues, it is necessary to educate children about the spread of contagious germs. This community service aims to help students understand how germs spread diseases. The activity was held at SDN 07 Palmerah for 2nd-grade students in the form of a health talk and a demonstration using a game about how germs are transmitted. The event occurred on January 30, 2024, from 8:00 to 9:00 AM WIB. The program started with an opening by the MC, followed by a pre-test where students, working in groups, placed images of locations where germs are found. After the pre-test, the session continued with a presentation on places where germs are found and how they spread a Q&A session, and a post-test. The results of the pre-test and post-test showed an increase in students' knowledge about the places where germs are found. Therefore, regular health education is necessary to prevent disease transmission among students in the classroom.